Lung Adenocarcinoma Presenting as Worsening of Chronic Neck Pain—A Cautionary Tale - Neeka N Akhavan; Tony S Brar; Edlira Maska (Clinical Medicine Insights: Case Reports, 2017)
Introduction: Neck pain is a common musculoskeletal problem that up to 70% of the world population will experience at some point in their lives. Intramedullary spinal cord metastasis is an exceedingly rare complication of malignancy that affects less than 1% of all patients with cancer. Case report: We report a case of a 61-year-old man who presented to primary care clinic with 1-month history of worsening neck pain with associated neurologic deficits. Despite initial conservative management, the patient continued to have progressive worsening of sensory and motor deficits. Magnetic resonance imaging of the cervical spine showed vasogenic edema of the brain and spinal cord and nodularity at the C4-C5 level. A computed tomography of the chest showed a dense lesion in the left lower lobe of the lung; histopathology of the biopsied specimen was consistent with moderately differentiated lung adenocarcinoma. Conclusions: A high index of suspicion is necessary when chronic neck pain acutely worsens, changes in character, or is accompanied by neurologic deficits. These clinical signs warrant further investigation into a secondary cause of neck pain. Intramedullary spinal cord metastases are rare complications of systemic cancer that commonly present with neck pain and upper extremity paraesthesias; early diagnosis and management are necessary to prevent complications such as spinal cord hemisection syndrome or spinal cord transection.